Monogenic diabetes: a new pathogenic variant of HNF1A gene. Issue 1 (20th January 2021) - Oliveira, Raquel Vilela; Bernardo, Teresa; Martins, Sandrina; Sequeira, Ana
Abstract : Maturity onset diabetes of the young defines a diabetes mellitus subtype, with no insulin resistance or autoimmune pancreatic β-cells dysfunction, that occurs by mutation in a single gene. A 13-year-old girl hospitalised due to hyperglycemia plus glycosuria without ketosis, and with normal glycated haemoglobin of 6.8%. She started a sugar-free fast-absorption diet and no insulin therapy was required. Fasting glucose was normal, but 2 hours after lunch she presented hyperglycemia as after 2 hours of an oral glucose tolerance test, with 217 mg/dL. Family history was positive for type 2 diabetes mellitus with an autosomal dominant pattern. She was discharged with fast-absorption sugar-free diet and low-dose of sulfonylurea. A genetic test was performed detecting a mutation in heterozygosity of HNF1A gene, compatible with the diagnosis of maturity onset diabetes of the young 3 (MODY3), not reported in the literature. Early recognition of signs and symptoms increase awareness of MODY. Genetic test allows confirmation and leads to optimised treatment.